Current Advances on Non-Melanoma Skin Cancer - Caruntu, Constantin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book is devoted to the design, application and characterization of thin films and structures, with special emphasis on optical applications. It comprises ten papers-five featured and five regular-authored by scientists all over the world. Diverse materials are studied and their possible applications are demonstrated and discussed-transparent conductive coatings and structures from ZnO doped with Al and Ga and Ti-doped SnO2, polymers and nanosized zeolite thin films for optical sensing, TiO2 with linear and nonlinear optical properties, organic diamagnetic materials, broadband optical coatings, CrWN glass molding coatings, and silicon on insulator waveguides.